Disability and Gender: A study of Lived Experiences of Economic Hardships Faced by Women with Disabilities from Sudurpaschim Province, Nepal - Niraula, Rupashree (International Journal of Social Sciences and Management, 2022)
According to the 2011 census, people with disabilities in Nepal are estimated to constitute 1.9% of the total population, out of which 3% are women with disabilities. Studies made on women with disabilities in Nepal show that they suffer violence and discrimination because of their subordinate position in society. Researches on women with disabilities in Nepal seem to focus on social barriers, exploitations and violence faced by them. In the short of researches and reports about the economic challenges faced by women with disabilities, this study uses the concept of intersectionality as a lens to analyze and interpret the economic hardships faced by women with disabilities from Sudurpaschim Province of Nepal. For the purpose of the study in-depth interviews were conducted among eight women with disabilities from Sudurpaschim Province. Though the study is made among women with disabilities from Sudurpaschim Province, the study does not intend to be location specific as such. The study is less about the geographical location of women with disabilities and more about their social location as women with disabilities. The study also delves into the social construction of gender and disability and how it has affected the lives of women with disabilities. Overall, the findings of the study give an impression of high economic dependency of women with disabilities and intensified economic hardships among women with severe form of disabilities. Int. J. Soc. Sc. Manage. Vol. 9, Issue-2: 55-62.